A 164-μW 915-MHz sub-sampling phase-tracking zero-IF receiver with 5-Mb/s data rate for short-range applications - Guo, Yanshu (2022)
This article presents a 915-MHz ultra-low-power (ULP) sub-sampling phase-tracking receiver (SSPT-RX). It is targeted for the power-constrained devices that need short range but medium high-speed data receiving, such as the multi-channel neural stimulator with arbitrary waveform generation. The zero-intermediate frequency (zero-IF) phase-tracking receiver (PT-RX) topology is adopted to simplify the sub-sampling RX architecture with direct demodulation of frequency-shift keying (FSK) signal while improving the image frequency issue. The frequency of local oscillator (LO) is reduced by ten times with the proposed architecture, which leads to greatly reduced power consumption. Fabricated in 65-nm CMOS process, the RX chip occupies an active area of 0.58 mm2. The RX consumes one of the lowest power consumptions of 164 μW from 0.5-/1-V supplies. It achieves an energy efficiency of 32.8 pJ/bit at a data rate of 5 Mb/s, which is improved by ∼5.6× compared to the stateof- the-art RXs. The measured sensitivity of 915-MHz FSK signal receiving is -69.5 dBm with an LO frequency of 91.5 MHz, which is 1/10 of the carrier frequency. The achieved RX sensitivity figure-of-merit (FoM) is 174.3 dB.